DETERMINAN STUNTING : BERAT BADAN BAYI RENDAH, PENDAPATAN KELUARGA, DAN ASUPAN SENG: DETERMINAN STUNTING : BERAT BADAN BAYI RENDAH, PENDAPATAN KELUARGA, DAN ASUPAN SENG - Desi Nurfita; Safira Intan Cahyani (Jurnal Ilmu Kesehatan Immanuel, 2025)
Background: Stunting is chronic malnutrition in children under five by measuring height based on age category <-2 standard deviation (SD). Indonesia has entered into multiple nutritional problems such as malnutrition and stunting. Stunting cases in Indonesia fall into the high category above the global average, which is more than 30%. This study aims to determine the relationship of low birth weight, family income, and zinc intake with the incidence of stunting in children under five in Indonesia. Methods: The research design used a systematic research meta-synthesis meta aggregation approach. Research subjects used search engines on Google Scholar and Elsevier with keywords: stunting factors, toddlers, Indonesia. The data collection used a systematic review protocol with screening stages, eligibility, and included. Results: The overall research data were found to be diverse, some stated that there was a relationship and there was no relationship seen from the p-value. Based on the proportion, the results showed that there was a relationship between LBW (87.5%), family income (75%), and zinc intake (75%) with the incidence of stunting. It is known that there is no correlation between LBW (12.5%), family income (12.5%), and zinc intake (25%) with the incidence of stunting. Conclusion: Most of the research results stated that there was a correlation between LBW, family income, and zinc intake with the incidence of stunting in children under five in Indonesia.